Magnetic multi-effect amphiphilic hybrid particle as well as preparation method and application thereof

By using magnetic multi-performance amphiphilic hybrid particles, using their unique structure and functions, the problem of difficult to deal with oil-containing wastewater containing partially hydrolyzed polyacrylamide in the prior art is solved, and efficient oil-water separation and wastewater treatment is achieved, and the particles can be reused, reducing costs.

CN119701882AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311262661.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently treat oil-containing wastewater containing partially hydrolyzed polyacrylamide in one step, especially when the pH value of the oil well discharging liquid changes greatly, the processing difficulty is significantly increased.

Method used

Magnetic multi-performance amphiphilic hybrid particles are used, which consists of the core and shell-sealed magnetic Fe3O4 particles and a silica/titanium dioxide hybrid shell with a fine pore structure. The outer surface of the shell includes both a hydrophilic and hydrophobic portion, and the inner surface and the inner core surface are grafted with polydiethylaminoethyl methacrylate (PDEAEMA).

Benefits of technology

Efficient adsorption and migration capture of partially hydrolyzed polyacrylamide is achieved, and oil-containing wastewater containing partially hydrolyzed polyacrylamide can be treated step by step efficiently. Due to the pH sensitivity of PDEAEMA, the particles can be reused, greatly reducing the material cost of wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004473443700000171
    Figure BDA0004473443700000171
  • Figure BDA0004473443700000181
    Figure BDA0004473443700000181
  • Figure BDA0004473443700000182
    Figure BDA0004473443700000182
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, and provides a magnetic multi-effect amphiphilic hybrid particle as well as a preparation method and application thereof. The magnetic multi-effect amphiphilic hybrid particle comprises a core-shell separated magnetic Fe3O4 particle core and a shell layer, the shell layer is a silicon dioxide / titanium dioxide hybrid shell layer with a fine hole structure, and the outer surface of the shell layer comprises a hydrophilic part and a hydrophobic part. Poly (diethylaminoethyl methacrylate) is grafted on the inner surface of the shell layer and the surface of the magnetic Fe3O4 particle inner core. The magnetic multi-effect amphiphilic hybrid particle provided by the invention has excellent emulsifying performance and can realize oil-water separation; meanwhile, partial hydrolyzed polyacrylamide can be selectively adsorbed, and oily sewage containing partial hydrolyzed polyacrylamide can be efficiently treated in one step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and more specifically to a magnetic multi-functional amphiphilic hybrid particle and a preparation method and application thereof. Background Art

[0002] As one of the most widely used varieties of water-soluble polymers, polyacrylamide has been widely used in fields such as oil extraction. In particular, the viscoelasticity of partially hydrolyzed polyacrylamide (HPAM) plays an extremely important role in controlling fluidity and improving oil recovery efficiency in tertiary oil recovery. With the increasing application of partially hydrolyzed polyacrylamide as a high molecular polymer for polymer flooding in my country's oilfield industry, the treatment of oil production wastewater containing partially hydrolyzed polyacrylamide has also received attention. However, the treatment of oily wastewater containing partially hydrolyzed polyacrylamide is more difficult than that of ordinary oily wastewater. Existing treatment methods generally require multi-step treatment to achieve the treatment standard of oily wastewater containing partially hydrolyzed polyacrylamide. How to remove partially hydrolyzed polyacrylamide in one step while achieving oil-water separation has always been a difficult problem in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0003] In addition, due to differences in oil wells and oil recovery operations, the pH value of the oil well recovery fluid varies greatly, and a large amount of wastewater is acidic or alkaline, which significantly increases the difficulty of its treatment. Summary of the invention

[0004] The purpose of the present invention is to provide a magnetic multi-functional amphiphilic hybrid particle and a preparation method thereof, so as to solve the technical problem in the prior art that oily wastewater containing partially hydrolyzed polyacrylamide is difficult to be treated in one step to meet the standards.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In the first aspect, the present invention provides a magnetic multi-functional amphiphilic hybrid particle, which comprises a core and shell of a magnetic Fe3O4 particle separated by a core-shell structure, wherein the shell is a silica / titanium dioxide hybrid shell with a micropore structure, and the outer surface of the shell comprises a hydrophilic part and a hydrophobic part, and the inner surface of the shell and the surface of the magnetic Fe3O4 particle core are grafted with polydiethylaminoethyl methacrylate (PDEAEMA).

[0007] It should be noted that the "micropore structure" described in the present invention includes the intermolecular gaps existing in the silica / titania macromolecular skeleton and the defects generated during the core-shell separation of the silica / titania hybrid shell from the magnetic Fe3O4 particle core, and even micropores and capillaries with a pore size of 0.5 to 50 nm.

[0008] The magnetic multi-functional amphiphilic hybrid particles provided by the present invention can protect the inner core of the magnetic Fe3O4 particles to a certain extent by coating a layer of silicon dioxide / titanium dioxide hybrid shell layer outside the inner core of the magnetic Fe3O4 particles. Within a certain time and a certain pH range, the inner core of the magnetic Fe3O4 particles can be protected from corrosion by hydrochloric acid, sulfuric acid, nitric acid or various alkaline reagents, thereby ensuring the industrial application of the magnetic particles.

[0009] The outer surface of the shell of the magnetic multi-functional amphiphilic hybrid particles provided by the present invention includes both a hydrophilic part and a hydrophobic part, so that the magnetic multi-functional amphiphilic hybrid particles have amphiphilicity. Compared with traditional homogeneous particles, they have more stable emulsification properties and can emulsify oil and water phases more stably and more widely to form a stable water-in-oil emulsion, providing a stability basis for the manipulation of emulsion droplets.

[0010] Moreover, the functional groups on the outer surface of the shell layer have electrostatic and other interactions with the partially hydrolyzed polyacrylamide, which promotes the adsorption of the partially hydrolyzed polyacrylamide on the outer surface of the shell layer. At the same time, after adsorption is achieved, the wetting effect of the internal structure of the amphiphilic hybrid particles on the partially hydrolyzed polyacrylamide adsorbed on the outer surface of the shell layer will promote the adsorption process of the partially hydrolyzed polyacrylamide into the shell layer. The polydiethylaminoethyl methacrylate (PDEAEMA) grafted on the inner surface of the shell layer and the surface of the inner core of the magnetic Fe3O4 particles forms a brush-like coating, which increases the specific surface area and enhances the hydrogen bond density. The microporous structure on the silica / titanium dioxide hybrid shell provides a channel for the migration and transmission of partially hydrolyzed polyacrylamide, and the weak acidic characteristics of partially hydrolyzed polyacrylamide are also conducive to its transfer and adsorption from the outside of the shell layer to the inside of the shell layer, thereby achieving the adsorption and migration capture of PDEAEMA on partially hydrolyzed polyacrylamide. The magnetic multi-functional amphiphilic hybrid particles provided by the present invention greatly improve the adsorption capacity and efficiency of partially hydrolyzed polyacrylamide through the combination of internal and external structures.

[0011] The magnetic multi-functional amphiphilic hybrid particles provided by the present invention can be reused multiple times. The magnetic multi-functional amphiphilic hybrid particles after use are washed and extracted with a benign solvent (such as ethanol) for partially hydrolyzed polyacrylamide to remove the adsorbed partially hydrolyzed polyacrylamide, so that the magnetic multi-functional amphiphilic hybrid particles can be reused to treat oily wastewater.

[0012] Moreover, since PDEAEMA is pH-sensitive, this property can be utilized to achieve repeated adsorption and desorption of partially hydrolyzed polyacrylamide by PDEAEMA through adjusting the pH, so that the magnetic multi-functional amphiphilic hybrid particles can be reused, greatly reducing the material cost of sewage treatment.

[0013] According to some embodiments of the present invention, the mass ratio of silicon dioxide to titanium dioxide in the shell layer is 1:10 to 10:1.

[0014] According to some embodiments of the present invention, the hydrophilic portion is obtained by modifying the outer surface with an amino-containing silane coupling agent.

[0015] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0016] The hydrophilic part of the outer surface of the shell is modified with 3-aminopropyltriethoxysilane to have amino groups, which can produce weak interactions with partially hydrolyzed polyacrylamide with carboxyl groups, thereby achieving adsorption of partially hydrolyzed polyacrylamide.

[0017] According to some embodiments of the present invention, the hydrophobic portion is obtained by modifying the outer surface of the shell layer with an alkyl-containing silane coupling agent.

[0018] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0019] According to some embodiments of the present invention, the area of ​​the hydrophilic portion accounts for 1 / 3 to 2 / 3 of the total area of ​​the outer surface of the shell layer.

[0020] According to some embodiments of the present invention, the particle size of the magnetic multi-functional amphiphilic hybrid particles is 100 nm<r≤1000 nm.

[0021] In a second aspect, the present invention provides a method for preparing magnetic multi-functional amphiphilic hybrid particles, comprising:

[0022] S1. Dispersing magnetic Fe3O4 particles in an alcohol solvent, adding tetraethyl orthosilicate and tetrabutyl titanate and stirring to obtain Fe3O4@SiO2 / TiO2 particles;

[0023] S2. Disperse Fe3O4@SiO2 / TiO2 particles in water, add paraffin, heat until the paraffin is completely melted, stir and mix, cool and filter, and obtain paraffin balls formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin;

[0024] S3. dispersing the paraffin balls into dimethyl sulfoxide, adding an amino-containing silane coupling agent, stirring the reaction, and re-dispersing the obtained solid particles into an alcohol solvent to obtain hydrophilic modified particles;

[0025] S4. The hydrophilic modified particles are dispersed in ethanol, an alkyl-containing silane coupling agent is added, and the reaction is stirred to obtain amphiphilic modified particles;

[0026] S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles;

[0027] S6. The core-shell separated amphiphilic modified particles are dispersed in an alcohol solvent, and 4-(chloromethyl)phenyltrimethoxysilane is added to undergo a modification reaction; and then a grafting reaction is carried out with diethylaminoethyl methacrylate to obtain magnetic multi-functional amphiphilic hybrid particles.

[0028] The preparation method of the magnetic multi-functional amphiphilic hybrid particles provided by the present invention is to use magnetic Fe3O4 particles as a carrier, use tetraethyl orthosilicate and tetrabutyl titanate to hydrolyze the surface of the magnetic Fe3O4 particles, and use a sol-gel process to coat the magnetic Fe3O4 particles to form an effective silicon / titanium-coated iron core-shell structure. Then, paraffin with a phase transition temperature of 52°C is used as the oil phase, and Fe3O4@SiO2 / TiO2 particles are used as solid particle emulsifiers to emulsify the oil-water phase at a temperature higher than the paraffin phase transition temperature to form a stable water-in-paraffin emulsion. After the emulsion is cooled, the paraffin phase solidifies and separates from the water phase to obtain paraffin balls formed by Fe3O4@SiO2 / TiO2 particles embedded in the paraffin surface, and the Fe3O4@SiO2 / TiO2 particles are partially embedded in the paraffin and partially exposed outside the paraffin. Then, the outer surface of the Fe3O4@SiO2 / TiO2 particles exposed to the paraffin was modified to be hydrophilic; the paraffin was removed to expose the part of the Fe3O4@SiO2 / TiO2 particles that was previously protected by the paraffin, and the outer surface of this part was modified to be hydrophobic, so as to obtain amphiphilic particles with both hydrophilic and hydrophobic parts on the particle surface. Then, an acid etching treatment was performed to reduce the size of the magnetic Fe3O4 particles, separate them from the shell layer, and generate a hollow structure between the core-shell structure. 4-(chloromethyl)phenyltrimethoxysilane was further used to modify the surface of the magnetic Fe3O4 particles and the inner surface of the shell layer with benzyl chloride [4-(chloromethyl)phenyl]. Benzyl chloride has high activity and can be grafted with polydiethylaminoethyl methacrylate (PDEAEMA) through ATRP (atom transfer radical polymerization) reaction to obtain magnetic multi-functional amphiphilic hybrid particles.

[0029] In the present invention, tetraethyl orthosilicate and tetrabutyl titanate are used to realize hydrolysis on the surface of magnetic Fe3O4 particles, and a relatively dense silica / titanium dioxide hybrid shell structure is formed on the surface of magnetic Fe3O4 particles through a sol-gel process, so as to protect the magnetic Fe3O4 particles inside. In addition, the silica / titanium dioxide hybrid shell in the present invention is a polymer formed by hydrolysis and condensation of tetraethyl orthosilicate and tetrabutyl titanate. Although the formed silica / titanium dioxide hybrid shell is relatively dense, in the sol-gel process of hydrolysis of tetraethyl orthosilicate and tetrabutyl titanate, the macromolecular skeleton formed by the condensation reaction still has intermolecular gaps, which ensures the smooth progress of the subsequent acid etching treatment, 4-(chloromethyl)phenyltrimethoxysilane modification and PDEAEMA grafting process.

[0030] In the present invention, after acid etching, the magnetic Fe3O4 particles are reduced in size, resulting in core-shell separation, which further causes defects in the shell layer. The microporous structure composed of the intermolecular voids in the shell layer provides a channel for the transmission and migration of partially hydrolyzed polyacrylamide to the interior of the shell layer.

[0031] In the present invention, acetic acid is used as the acid etching agent, which can slow down the etching process, ensure that the etching process is controllable, and make the surface of the inner core of the magnetic Fe3O4 particles smoother; if hydrochloric acid, sulfuric acid, etc. are used, it is difficult to control the etching process, which can easily lead to excessive etching, thereby weakening the magnetism of the particles or even completely disappearing.

[0032] According to some embodiments of the present invention, the alcohol solvent includes at least one of methanol, ethanol, propanol, butanol, isopropanol, and cyclohexanol.

[0033] According to some embodiments of the present invention, the stirring and mixing speed in step S2 is 1000-5000 rpm.

[0034] In the present invention, the stirring speed in step S2 will directly affect the emulsification process of the particulate emulsifier (Fe3O4@SiO2 / TiO2 particles), and directly lead to the stabilization of the emulsion interface by the particulate emulsifier. When the stirring speed is less than 1000rpm, the stirring speed is too low, and the particulate emulsifier is difficult to deliver to the interface, the interface cannot be stabilized, and the emulsion is easy to break; when the stirring speed is greater than 5000rpm, the stirring speed is too high, and the particulate emulsifier is forced to pull at the interface, which easily leads to interface instability and emulsion breaking. Therefore, in order to ensure emulsification and interface stability, it is advisable that the stirring speed in step S2 is controlled at 1000-5000rpm.

[0035] According to some embodiments of the present invention, the stirring and mixing time in step S2 is 3 to 5 minutes.

[0036] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0037] The local hydrophilic modification of the outer surface of Fe3O4@SiO2 / TiO2 particles was carried out in dimethyl sulfoxide using 3-aminopropyltriethoxysilane. The sol-gel composite on the outer surface of Fe3O4@SiO2 / TiO2 particles exposed to paraffin was achieved through a hydrolysis process, and amino groups were modified on one side of the outer surface of Fe3O4@SiO2 / TiO2 particles.

[0038] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0039] The local hydrophobic modification of the outer surface of Fe3O4@SiO2 / TiO2 particles using n-octyltriethoxysilane is first performed by removing paraffin with an alcohol solvent, so that the Fe3O4@SiO2 / TiO2 particles embedded in the paraffin and the protected parts are exposed, and then the exposed parts of the Fe3O4@SiO2 / TiO2 particles from the embedded paraffin are subjected to the hydrolysis process of n-octyltriethoxysilane to achieve surface sol-gel composite, and the other side of the outer surface of the Fe3O4@SiO2 / TiO2 particles is modified with n-octyl groups.

[0040] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles, tetraethyl orthosilicate and tetrabutyl titanate is 1:(0.1-1):(0.1-1).

[0041] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the paraffin is 1:(10-200).

[0042] According to some embodiments of the present invention, the mass ratio of paraffin to water is 1:(2-10).

[0043] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01).

[0044] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01).

[0045] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01).

[0046] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the diethylaminoethyl methacrylate is 1:(0.02-0.1).

[0047] According to some embodiments of the present invention, the particle size of the magnetic Fe3O4 particles is 100-500 nm.

[0048] According to some embodiments of the present invention, the particle size ratio of the magnetic Fe3O4 particles to the core of the magnetic Fe3O4 particles is 100:(10-99).

[0049] In the present invention, if the particle size ratio of the magnetic Fe3O4 particles to the magnetic Fe3O4 particle core is less than 100:99, the gap between the shell and the magnetic Fe3O4 particle core is too small, which will affect the adsorption capacity of the magnetic multi-functional amphiphilic hybrid particles to partially hydrolyzed polyacrylamide; if the particle size ratio of the magnetic Fe3O4 particles to the magnetic Fe3O4 particle core is greater than 100:10, the size of the magnetic Fe3O4 particle core is too small, which will lead to serious magnetic attenuation and difficulty in achieving magnetic manipulation of the external magnetic field.

[0050] According to some embodiments of the present invention, the grafting reaction includes: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction in a nitrogen atmosphere at 60-100°C.

[0051] According to some embodiments of the present invention, the solvent used in the grafting reaction includes at least one of water, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0052] According to some embodiments of the present invention, the stirring reaction time in step S3 is 5 to 6 hours.

[0053] According to some embodiments of the present invention, the stirring reaction time in step S4 is 5 to 6 hours.

[0054] According to some embodiments of the present invention, the magnetic Fe3O4 particles and tetrabutyl titanate are dispersed in an alcohol solvent by ultrasound and stirring for 12 to 24 hours. Preferably, the ultrasound frequency is 60 to 80 Hz and / or the stirring speed is 50 to 100 rpm.

[0055] According to some embodiments of the present invention, the Fe3O4@SiO2 / TiO2 particles are dispersed in water by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0056] According to some embodiments of the present invention, the paraffin balls are dispersed in dimethyl sulfoxide by stirring, and preferably, the stirring speed is 50 to 100 rpm;

[0057] According to some embodiments of the present invention, the hydrophilic modified particles are dispersed in the alcohol solvent by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 200-300 rpm.

[0058] According to some embodiments of the present invention, mixing the amphiphilic modified particles with acetic acid for 8-12 hours comprises: dispersing the amphiphilic modified particles in water, adding acetic acid, and mixing for 8-12 hours by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0059] In a third aspect, the present invention provides a magnetic multi-functional amphiphilic hybrid particle prepared by the preparation method described in the second aspect.

[0060] In a fourth aspect, the present invention provides the use of the magnetic multi-functional amphiphilic hybrid particles described in the first aspect or the magnetic multi-functional amphiphilic hybrid particles described in the third aspect in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0061] The beneficial effects of the present invention are at least:

[0062] (1) The magnetic multi-functional amphiphilic hybrid particles provided by the present invention have excellent emulsification properties. The droplets stabilized by the magnetic multi-functional amphiphilic hybrid particles can be manipulated by an external magnetic field to achieve the enrichment and migration of oil droplets, thereby achieving oil-water separation; at the same time, they can selectively adsorb partially hydrolyzed polyacrylamide, and can efficiently treat oily wastewater containing partially hydrolyzed polyacrylamide in one step.

[0063] (2) The magnetic multi-functional amphiphilic hybrid particles provided by the present invention can be reused multiple times, and the adsorption capacity for partially hydrolyzed polyacrylamide will not decrease significantly, which can greatly reduce the material cost of sewage treatment.

[0064] (3) The silica / titanium dioxide hybrid shell of the magnetic multi-functional amphiphilic hybrid particles provided by the present invention can improve the acid resistance and alkali resistance of the amphiphilic hybrid particles to a certain extent, so that they can be used to treat sewage with more complex composition.

[0065] (4) The preparation method of the magnetic multi-functional amphiphilic hybrid particles provided by the present invention has a simple process, low cost and readily available raw materials, and can achieve industrial mass production at the ton level. DETAILED DESCRIPTION

[0066] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0067] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0068] Example 1

[0069] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1 g of ethyl orthosilicate and 1 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0070] S2. Disperse the Fe3O4@SiO2 / TiO2 particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time. Maintain ultrasound and stirring to promote the dispersion of Fe3O4@SiO2 / TiO2 particles. Raise the water temperature to 80℃, add 20g paraffin (phase transition temperature is 52℃), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin.

[0071] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and use an overhead stirrer to slowly stir the dispersion at a speed of 50 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and use an external magnetic field to separate the solid particles to obtain Fe3O4@SiO2 / TiO2-NH2 particles with amino groups modified on one side of the surface.

[0072] S4. Disperse Fe3O4@SiO2 / TiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 60 Hz ultrasound. Add 20 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field and dry them in the natural state to obtain

[0073] C8-Fe3O4@SiO2 / TiO2-NH2 particles.

[0074] S5. The C8-Fe3O4@SiO2 / TiO2-NH2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm, while ultrasound was applied at 60 Hz to obtain core-shell separated C8-Fe3O4@SiO2 / TiO2-NH2 particles;

[0075] S6. The core-shell separated C8-Fe3O4@SiO2 / TiO2-NH2 particles were dispersed in 100 mL of ethanol, 10 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 100 rpm for 12 h to obtain modified C8-Fe3O4@SiO2 / TiO2-NH2 particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the modified C8-Fe3O4@SiO2 / TiO2-NH2 particles were added, and 0.1 g of DEAEMA was added. N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 100 rpm for 3 h. After the reaction, magnetic multi-functional amphiphilic hybrid particles were obtained.

[0076] Example 2

[0077] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 0.3 g of ethyl orthosilicate and 0.3 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0078] S2. Disperse the Fe3O4@SiO2 / TiO2 particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time. Maintain ultrasound and stirring to promote the dispersion of Fe3O4@SiO2 / TiO2 particles. Raise the water temperature to 80℃, add 40g paraffin (phase transition temperature is 52℃), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 1000rpm, and continue stirring for 5min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from water. Spread the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin.

[0079] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and use an overhead stirrer to slowly stir the dispersion at a speed of 50 rpm. Add 3 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and use an external magnetic field to separate the solid particles to obtain Fe3O4@SiO2 / TiO2-NH2 particles with amino groups modified on one side of the surface.

[0080] S4. Disperse Fe3O4@SiO2 / TiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and add 60 Hz ultrasound. Add 3 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field and dry them in the natural state to obtain

[0081] C8-Fe3O4@SiO2 / TiO2-NH2 particles.

[0082] S5. The C8-Fe3O4@SiO2 / TiO2-NH2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm, while ultrasound was applied at 60 Hz to obtain core-shell separated C8-Fe3O4@SiO2 / TiO2-NH2 particles;

[0083] S6. The core-shell separated C8-Fe3O4@SiO2 / TiO2-NH2 particles were dispersed in 100 mL of ethanol, 3 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 100 rpm for 12 h to obtain modified C8-Fe3O4@SiO2 / TiO2-NH2 particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the modified C8-Fe3O4@SiO2 / TiO2-NH2 particles were added, and 0.04 g of DEAEMA was added. N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 100 rpm for 3 h. After the reaction, magnetic multi-functional amphiphilic hybrid particles were obtained.

[0084] Example 3

[0085] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 2 g of tetraethyl orthosilicate and 2 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0086] S2. Disperse Fe3O4@SiO2 / TiO2 particles into 200mL of water, add 60Hz ultrasound and 100rpm overhead stirring, and maintain ultrasound and stirring to promote the dispersion of Fe3O4@SiO2 / TiO2 particles. Raise the water temperature to 80℃, add 20g paraffin (phase transition temperature is 52℃), and continue stirring until the paraffin is completely melted. Turn off ultrasound and increase the stirring speed to 5000rpm, and continue stirring for 4min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin.

[0087] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and use an overhead stirrer to slowly stir the dispersion at a speed of 50 rpm. Add 10 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and use an external magnetic field to separate the solid particles to obtain Fe3O4@SiO2 / TiO2-NH2 particles with amino groups modified on one side of the surface.

[0088] S4. Disperse Fe3O4@SiO2 / TiO2-NH2 particles in 100 mL of ethanol and stir the dispersion with an overhead stirrer at 300 rpm and 60 Hz ultrasound. Add 10 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field and dry them in the air to obtain

[0089] C8-Fe3O4@SiO2 / TiO2-NH2 particles.

[0090] S5. The C8-Fe3O4@SiO2 / TiO2-NH2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm, while ultrasound was applied at 60 Hz to obtain core-shell separated C8-Fe3O4@SiO2 / TiO2-NH2 particles;

[0091] S6. The core-shell separated C8-Fe3O4@SiO2 / TiO2-NH2 particles were dispersed in 100 mL of ethanol, 15 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 100 rpm for 12 h to obtain modified C8-Fe3O4@SiO2 / TiO2-NH2 particles; 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine were dissolved in 50 mL of DMF, the modified C8-Fe3O4@SiO2 / TiO2-NH2 particles were added, and 0.2 g of DEAEMA was added. N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 100 rpm for 3 h. After the reaction, magnetic multi-functional amphiphilic hybrid particles were obtained.

[0092] Example 4

[0093] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1 g of ethyl orthosilicate and 1 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0094] S2. Disperse Fe3O4@SiO2 / TiO2 particles into 200mL of water, add 60Hz ultrasound and 100rpm overhead stirring, keep ultrasound and stirring to promote the dispersion of Fe3O4@SiO2 / TiO2 particles. Raise the water temperature to 80℃, add 20g paraffin (phase transition temperature is 52℃), and continue stirring until the paraffin is completely melted. Turn off ultrasound and increase the stirring speed to 500rpm.

[0095] Since the stirring speed is too low, the particles cannot be delivered to the oil-water interface by mechanical force, the silicon / titanium-coated iron magnetic particles cannot be stabilized at the oil-water interface, the oil-water two phases cannot be stably emulsified, the water phase and the oil phase remain two phases, and the paraffin ball powder formed by the silicon / titanium-coated iron magnetic particles embedded in the paraffin surface cannot be obtained.

[0096] Example 5

[0097] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1 g of ethyl orthosilicate and 1 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0098] S2. Disperse Fe3O4@SiO2 / TiO2 particles into 200mL of water, add 60Hz ultrasound and 100rpm overhead stirring, keep ultrasound and stirring to promote the dispersion of Fe3O4@SiO2 / TiO2 particles. Raise the water temperature to 80℃, add 20g paraffin (phase transition temperature is 52℃), and continue stirring until the paraffin is completely melted. Turn off ultrasound and increase the stirring speed to 6000rpm.

[0099] Due to the high stirring speed, although the silicon / titanium-coated iron magnetic particles were delivered to the oil-water interface by mechanical force to achieve emulsification, the too-fast mechanical stirring caused the particles to peel off at the interface, making the interface unstable and causing emulsion demulsification. It was impossible to produce the paraffin ball powder formed by the silicon / titanium-coated iron magnetic particles embedded in the paraffin surface.

[0100] Comparative Example 1

[0101] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1 g of ethyl orthosilicate and 1 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0102] S2. Disperse the Fe3O4@SiO2 / TiO2 particles into 200mL of water, and add 60Hz ultrasound and 100rpm overhead stirring at the same time. Maintain ultrasound and stirring to promote the dispersion of Fe3O4@SiO2 / TiO2 particles. Raise the water temperature to 80℃, add 20g paraffin (phase transition temperature is 52℃), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin.

[0103] S3. Disperse the paraffin ball powder in 100 mL of dimethyl sulfoxide, and use an overhead stirrer to slowly stir the dispersion at a speed of 50 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 100 mL of ethanol, dissolve the paraffin, and use an external magnetic field to separate the solid particles to obtain Fe3O4@SiO2 / TiO2-NH2 particles with amino groups modified on one side of the surface.

[0104] S4. Disperse Fe3O4@SiO2 / TiO2-NH2 particles in 100 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 60 Hz ultrasound. Add 20 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field and dry them in a natural state to obtain particles.

[0105] Comparative Example 2

[0106] S1. Disperse 2 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 200 mL of ethanol, add 1 g of ethyl orthosilicate and 1 g of tetrabutyl titanate, add 60 Hz ultrasound and 100 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate Fe3O4@SiO2 / TiO2 particles.

[0107] S2. The Fe3O4@SiO2 / TiO2 particles were dispersed in 100 mL of water, 2 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 100 rpm, while ultrasound was applied at 60 Hz to obtain core-shell separated Fe3O4@SiO2 / TiO2 particles;

[0108] S3. Disperse the core-shell separated Fe3O4@SiO2 / TiO2 particles in 100 mL of ethanol, add 10 mg of 4-(chloromethyl)phenyltrimethoxysilane, and stir at 100 rpm for 12 h to obtain modified Fe3O4@SiO2 / TiO2 particles; dissolve 0.02 g of cuprous chloride and 0.02 g of 2,2-bipyridine in 50 mL of DMF, add the above-mentioned modified Fe3O4@SiO2 / TiO2 particles, and add 0.1 g of DEAEMA, and introduce N2 to deoxygenate for 30 min, heat to 80°C, stir at 100 rpm for 3 h, and obtain particles after the reaction is completed.

[0109] Comparative Example 3

[0110] The particles were prepared by referring to the preparation method of Example 1, except that the acetic acid was replaced by an equal volume of dilute hydrochloric acid (pH 6).

[0111] Comparative Example 4

[0112] The particles were prepared by referring to the preparation method of Example 1, except that acetic acid was replaced by an equal volume of sulfuric acid.

[0113] Performance Evaluation

[0114] (I) The particle size of the particles of each embodiment and comparative example was measured using a scanning electron microscope, and the results are shown in the following table:

[0115]

[0116]

[0117] (II) Wastewater treatment effect

[0118] 1 kg of the particles prepared in each embodiment and comparative example were added to 10 t of partially hydrolyzed polyacrylamide oily wastewater (COD value was 2020, petroleum pollutant content was 52.3 mg / L, and partially hydrolyzed polyacrylamide content was 103.05 mg / L), and the oily wastewater was emulsified by stirring at a speed of 1000 rpm for 1 min using a shearing machine; then the migration and enrichment of the emulsified oil droplets of the magnetic particles were achieved by controlling the external magnetic field. The treated wastewater was tested, and the test method is shown in the following table:

[0119]

[0120] The test results are shown in the following table:

[0121]

[0122] (III) Cyclic performance

[0123] The magnetic multi-functional amphiphilic hybrid particles are washed and regenerated by a solvent method, thereby realizing the recycling of the magnetic multi-functional amphiphilic hybrid particles. The specific treatment method includes: collecting the magnetic multi-functional amphiphilic hybrid particles of Example 1 after wastewater treatment, washing them with ethanol, the mass ratio of ethanol to particles is 10:1, and then freeze-drying them after washing to obtain regenerated particles.

[0124] The regenerated particles were used to repeat the treatment process of partially hydrolyzed polyacrylamide-containing oily wastewater in step (ii), and the indicators of the treated wastewater were similar to the treatment effect of the first wastewater treatment using the magnetic multi-functional amphiphilic hybrid particles in Example 1. The magnetic multi-functional amphiphilic hybrid particles can be recycled for more than 100 times, and the removal effect of COD, petroleum and partially hydrolyzed polyacrylamide will not be significantly deteriorated.

[0125] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A magnetic multi-functional amphiphilic hybrid particle, characterized in that: The magnetic multi-functional amphiphilic hybrid particles include a core and a shell of a core-shell separated magnetic Fe3O4 particle, wherein the shell is a silicon dioxide / titanium dioxide hybrid shell with a microporous structure, the outer surface of the shell includes a hydrophilic part and a hydrophobic part, and the inner surface of the shell and the surface of the core of the magnetic Fe3O4 particle are grafted with polydiethylaminoethyl methacrylate.

2. The magnetic multi-functional amphiphilic hybrid particles according to claim 1, characterized in that: The hydrophilic part is obtained by modifying the outer surface of the shell layer with an amino-containing silane coupling agent; preferably, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the hydrophobic part is obtained by modifying the outer surface of the shell layer with an alkyl-containing silane coupling agent; preferably, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

3. The magnetic multi-functional amphiphilic hybrid particles according to claim 1 or 2, characterized in that: The particle size of the magnetic multi-functional amphiphilic hybrid particles is 100nm<r≤1000nm.

4. A method for preparing magnetic multi-functional amphiphilic hybrid particles, characterized in that: include: S1. Dispersing magnetic Fe3O4 particles in an alcohol solvent, adding tetraethyl orthosilicate and tetrabutyl titanate and stirring to obtain Fe3O4@SiO2 / TiO2 particles; S2. Disperse Fe3O4@SiO2 / TiO2 particles in water, add paraffin, heat until the paraffin is completely melted, stir and mix, cool and filter, and obtain paraffin balls formed by Fe3O4@SiO2 / TiO2 particles embedded on the surface of paraffin; S3. dispersing the paraffin balls into dimethyl sulfoxide, adding an amino-containing silane coupling agent, stirring the reaction, and re-dispersing the obtained solid particles into an alcohol solvent to obtain hydrophilic modified particles; S4. The hydrophilic modified particles are dispersed in ethanol, an alkyl-containing silane coupling agent is added, and the reaction is stirred to obtain amphiphilic modified particles; S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles; S6. The core-shell separated amphiphilic modified particles are dispersed in an alcohol solvent, and 4-(chloromethyl)phenyltrimethoxysilane is added to undergo a modification reaction; and then a grafting reaction is carried out with diethylaminoethyl methacrylate to obtain magnetic multi-functional amphiphilic hybrid particles.

5. The preparation method according to claim 4, characterized in that: The stirring and mixing speed in step S2 is 1000-5000 rpm, and preferably, the stirring and mixing time in step S2 is 3-5 min; And / or, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

6. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the magnetic Fe3O4 particles, tetraethyl orthosilicate and tetrabutyl titanate is 1:(0.1-1):(0.1-1); and / or, the mass ratio of the magnetic Fe3O4 particles to the paraffin is 1:(10-200); And / or, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01); and / or, the mass ratio of the magnetic Fe3O4 particles to the 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to the diethylaminoethyl methacrylate is 1:(0.02-0.1).

7. The preparation method according to any one of claims 4 to 6, characterized in that: The particle size of the magnetic Fe3O4 particles is 100 to 500 nm; And / or, the particle size ratio of the magnetic Fe3O4 particles to the core of the magnetic Fe3O4 particles is 100:(10-99).

8. The preparation method according to any one of claims 4 to 7, characterized in that: The grafting reaction comprises: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction under a nitrogen atmosphere at 60-100° C.

9. A magnetic multi-functional amphiphilic hybrid particle prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the magnetic multi-functional amphiphilic hybrid particles according to any one of claims 1 to 3 or the magnetic multi-functional amphiphilic hybrid particles according to claim 9 in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

Citation Information

Patent Citations

  • Compound Janus colloid particle and modified Janus colloid particle as well as preparation methods thereof

    CN101885813A

  • Method for preparing silicon dioxide core-shell materials with core-shell spacing

    CN104961133A

  • A mesoporous magnetic polymer composite sphere, a preparing method thereof and applications of the composite sphere

    CN105435753A

  • Amphiphilic and magnetic nano-particles and preparation method thereof

    CN110211757A

  • Magnetic response Janus nano-particles based on oil-in-water high internal phase emulsification and preparation method of magnetic response Janus nano-particles

    CN112812760A